Pendampingan Keterampilan Digital Content Creator Santri Sebagai Media Dakwah Era Digital - Herdiana, Aan; Wakhyudi, Yukhsan; Anis, Aswhar; Kusuma Pratiwi, Intan; Hasqia Zaeni, Fenita (JCSE: Journal of Community Service and Empowerment, 2023)
Islamic boarding schools should take advantage of the potential of social media as a means or medium of da'wah to the community. In today's information age, da'wah is not only limited to lecturing on the pulpit. In the present era, the pulpit is in your hands. Today's modern society requires virtual religious instructions. In addition, to save the public from irresponsible, hoax, hateful, and other negative information, Islamic boarding schools are at the forefront. In this context, the role of Islamic boarding schools to spread their da'wah in virtual space is highly expected by the community. This community service activity (PKM) seeks to solve problems with partners, namely Miftahul Huda Islamic Boarding School in Pesawahan Village, Rawalo District, Banyumas Regency, in order to strengthen the position and potential of Islamic boarding schools in the virtual world by producing interesting, useful and positive content. as a means of da'wah in the digital era to the public. The purpose of this activity is to develop the skills of students as content creators in creating interesting and useful content as a medium of da'wah in the digital era.